Law Enforcement Against Medical Personnel as Perpetrators of Fraud in the National Health Insurance Program - Priscilia, Viona; Kantikha, I Made; Prasetyo, Boedi (PSPP JOURNALS, 2025)
JKN is program issued by the government aimed providing certainty in providing comprehensive health services for all Indonesian citizens. However, since JKN was first implemented until now, many challenges have been experienced, one of which is the large number of fraudulent acts in its implementation dominated by JKN participants themselves. Therefore, this research aims to find out. what prevention efforts have been carried out, the application of current sanctions, and how to update the application of sanctions for JKN participants who commit fraud in the implementation of JKN in Indonesia. This research is normative legal research referring to legal sources, especially statutory regulations relating to acts of fraud in healthservice programs. Legal sources in this writing consist of primary legal materials and secondary legal materials. The data collection technique used is library research. The data analysis techniques carried out in this research will go through a qualitative processing and analysis stage. The results of this research show that prevention efforts that have been carriedout by the government include reporting suspected fraud to the Fraud Prevention and Handling Team, maintaining the confidentiality of residence identity and JKN KIS cards so that they are not misused, and complying with all existing regulations, then implementing sanctions against Currently, acts of fraud only take the form of administrative sanctions,therefore the effort to reform the application of sanctions is to include the concept of criminalization in the form of imprisonment in order to catch fraudsters in the implementation of JKN in Indonesia.